Are Health Factors Important for Regional Growth and Convergence? An Empirical Analysis for the Portuguese Districts - Poças, Ana Isabel (2016)
The aim of this study is to analyse the impact of health factors on economic growth and convergence across the Portuguese regions at the district level. Like education, health factors could be important for explaining the growth performance of regions through the increase in labour productivity. Therefore, human capital can be seen in a broader perspective encompassing not only educational qualifications but also health conditions. Although this is not a new idea, empirical evidence at a regional level is not robust supporting this issue, with few exceptions. With this study we try to fill this gap and bring additional evidence of the relevance of health on regional growth considering the Portuguese districts. We employ a panel data approach for the period 1996-2006 taking into account specific regional differences. We also analyse whether there are differences between the littoral (coastal) and the interior (in-land) districts in what concerns health conditions and how they affect their convergence process.